Estimated Impact of Emergency Medical Service Triage of Stroke Patients on Comprehensive Stroke Centers: An Urban Population-Based Study. Issue 8 (August 2017) - Katz, Brian S.; Adeoye, Opeolu; Sucharew, Heidi; Broderick, Joseph P.; McMullan, Jason; Khatri, Pooja; Widener, Michael; Alwell, Kathleen S.; Moomaw, Charles J.; Kissela, Brett M.; Flaherty, Matthew L.; Woo, Daniel; et al.
Abstract : Background and Purpose—: The American Stroke Association recommends that Emergency Medical Service bypass acute stroke–ready hospital (ASRH)/primary stroke center (PSC) for comprehensive stroke centers (CSCs) when transporting appropriate stroke patients, if the additional travel time is ⩽15 minutes. However, data on additional transport time and the effect on hospital census remain unknown. Methods—: Stroke patients ≥20 years old who were transported from home to an ASRH/PSC or CSC via Emergency Medical Service in 2010 were identified in the Greater Cincinnati area population of 1.3 million. Addresses of all patients' residences and hospitals were geocoded, and estimated travel times were calculated. We estimated the mean differences between the travel time for patients taken to an ASRH/PSC and the theoretical time had they been transported directly to the region's CSC. Results—: Of 929 patients with geocoded addresses, 806 were transported via Emergency Medical Service directly to an ASRH/PSC. Mean additional travel time of direct transport to the CSC, compared with transport to an ASRH/PSC, was 7.9±6.8 minutes; 85% would have ⩽15 minutes added transport time. Triage of all stroke patients to the CSC would have added 727 patients to the CSC's census in 2010. Limiting triage to the CSC to patients with National Institutes of Health Stroke Scale score of ≥10 within 6 hours of onset would have added 116 patients (2.2 per week) to the CSC's annual census. Conclusions—: Emergency Medical Service triage to CSCs based on stroke severity and symptom duration may be feasible. The impact on stroke systems of care and patient outcomes remains to be determined and requires prospective evaluation.